Understanding Al-Ghazali's Idea of Bliss in the Book of Kimiya' As-Sa'adah in Its Importance to Modern Humans - Halim Iskandar (International Journal of Contemporary Sciences (IJCS), 2024)
One can find true happiness by changing the conditions within each individual. This research aims to determine Al-Ghazali's concept of happiness in the book Kimiyah As-Sa'adah and its application in modern society. This research uses document research as the method. The source used is Imam Al-Gazali's main work entitled Kimiya as-Sa'adah and this research is secondary. Based on the findings of this research, happiness according to Al-Ghazali in the book Kimiya AS-Sa'adah is the achievement of purity of soul and heart, not happiness that is based on objects or the world. There are four different ways used to achieve happiness in modern times, namely: knowing Allah, knowing the goodness of this world and the hereafter and knowing yourself